Developing scales for measuring teachers' acceptance of the environmental education (EE) kit: a pilot study in Malaysian schools - Sulaiman, Siti Hajar; Tengku Ismail, Tengku Hanidza; Juahir, Hafizan; Harun, Rosta (IDOSI Publications, 2013)
Three indicators were developed to measure the teachers’ acceptability of the EE Kit: perception, attitude and receptiveness. In this study, 81 teachers teaching Science, Geography, English and Malay Language from four public schools in Peninsular Malaysia who received the EE Kit participated. This study aimed to describe and analyze the experience of using the EE Kit for teaching environmental education component in the classroom. This study found that, 75/81 (92.59%) knew about the EE Kit, 64/81 (79.01%) used the EE Kit and 11 (13.58%) who knew about the kit but did not use it. Overall, teachers are in favor of the use of the EE Kit in the classroom and recommend it to be used in all schools in Malaysia. Two important issues were highlighted, that is, the need for teacher training on the use of EE Kit and the use of simple English language to suit the need of rural students.